Update on Pulmonary Langerhans Cell Histiocytosis - Radzikowska, Elzbieta (Frontiers in Medicine, 2021)
Pulmonary Langerhans' cell histiocytosis (PLCH) has unknown cause, and is a rare neoplastic disorder, characterised by the infiltration of the lungs and various organs by the bone marrow derived Langerhans' cells with accompany strong inflammatory response. These cells carry mutations of BRAF gene and/or NRAS, KRAS and MAP2K1 genes. PLCH occurs predominantly in young smokers, without gender predominance. Lungs might be involved as an isolated organ or as part of multiorgan disease. High-resolution computed chest tomography plays an outstanding role in PLCH diagnosis. The typical radiological picture of PLCH is the presence of small intralobular nodules, ‘tree in bud' opacities, cavitated nodules, thin- and thick-walled cysts, frequently confluent. Histological examination of lesion, and demonstration of characteristic eosinophilic granulomas with presence of LC cells display antigen CD1a or CD207 in immunohistochemistry are required for definite diagnosis. Smoking cessation is the most important recommendation for PLCH patients, but treatment of progressive PLCH, and multisystem disease is based on chemotherapy. Recently, new targeted therapies have been implemented.